Dialoguing partnerships: An analysis of the dialogue assumptions of the Danish partnership for dialogue and reform - Marie-Louise Wegter; Karina Pulz (Danish Institute for International Studies (DIIS), 2010)
In 2003, the Danish government launched the Partnership for Dialogue and Reform (PDR) with the dual objective of 1) establishing a basis for improved dialogue, understanding and cooperation between Denmark and the Arab region; and 2) supporting existing local reform processes in the Middle East and North Africa. With the first objective, which is the focus of this study, PDR was intended to demonstrate the trivialization of Huntington's thesis of a clash of civilizations that Al Qaeda, only few years before, had brought back to the limelight of international politics and endeavoured to prove. PDR was to show populations in Europe and the Arab world that there was indeed a strong, shared agenda between the so-called West and the mother-region of the Islamic world and that mutual misconceptions and prejudice could be overcome through the joined pursuit of this agenda of progress.
Keywords: 300; Internationale Beziehungen; Kooperation; Dänemark; Nordafrika; Mittlerer Osten